Surface engineering of oncolytic adenovirus for a combination of immune checkpoint blockade and virotherapy. (18th August 2021) - Lv, Peng; Chen, Xiaomei; Fu, Shiying; Ren, En; Liu, Chao; Liu, Xuan; Jiang, Lai; Zeng, Yun; Wang, Xiaoyong; Liu, Gang
Abstract : A new strategy to coat oncolytic viruses in a bioengineered cell membrane with PD1 expression provides a clinical basis for combining oncolytic virotherapy with checkpoint inhibitors, resulting in a stronger antitumor immunity response. Abstract : Advances in the development of modern cancer immunotherapy and immune checkpoint inhibitors have dramatically changed the landscape of cancer treatment. However, most cancer patients are refractory to immune checkpoint inhibitors because of low lymphocytic tumor infiltration and PD-L1 expression. Evidence suggests that viral oncolysis and immune checkpoint inhibitors have a synergistic effect that can improve the response to immune checkpoint inhibitors. In this study, we developed bioengineered cell membrane nanovesicles (PD1-BCMNs) with programmed cell death protein 1 (PD-1) to harbor oncolytic adenovirus (OA) and achieve a combination of immune checkpoint blockade and oncolytic virotherapy in one particle for cancer treatment. PD1-BCMNs could specifically deliver OA to tumor tissue; the infectivity and replication ability of the OA was preserved in the presence of neutralizing antibodies in vitro and in vivo. Selective oncolytic effects with oncolytic adenovirus led to an up-regulated expression of PD-L1 in the tumor microenvironment, turning immunologically 'cold' tumors into immunologically 'hot' tumors, presenting more targets for further enhanced target delivery. Notably, PD1-BCMNs@OA could effectively activate tumor-infiltrating T cells and elicit a strong anti-tumor immune response. Thus, PD1-BCMNs@OA may provide a clinical basis for combining oncolytic virotherapy with checkpoint inhibitors, enhancing the oncolytic adenovirus targeted delivery and significantly enhancing T cell immune responses, resulting in a stronger antitumor immunity response.